CONTEMPORARY CHALLENGES IN LATIN AMERICAN ADMINISTRATIVE JUSTICE - R. Perlingeiro (BRICS Law Journal, 2016)
This study consists of a critical comparative analysis of the administrative justice systems in eighteen Latin-American signatory countries of the American Convention on Human Rights (Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, El Salvador, Ecuador, Guatemala, Honduras, Mexico, Nicaragua, Panama, Paraguay, Peru, the Dominican Republic, Uruguay, and Venezuela). According to this article, the excessive litigation in Latin-American courts that has seriously hampered the effectiveness of the administrative justice systems may be explained as follows: as former Iberian colonies, the aforementioned countries have a Continental European legal culture originating in civil law but nevertheless have improperly integrated certain aspects of the unified judicial system (generalized courts) typical of administrative law in common-law countries. This situation, according to the author, could be rectified through strengthening the public administrative authorities with respect to their dispute-resolution and purely executive functions by endowing them with prerogatives to act independently and impartially, oriented by the principle of legality understood in the sense of supremacy of fundamental rights, in light of the doctrine of diffuse conventionality control adopted by the InterAmerican Court of Human Rights.